The Effect of Teacher - Mediated Vocabulary Discussions During Read Alouds - Leanne Radabaugh (My University, 2015)
This action research study utilized a quasi-experimental pre-/post-test design to examine effect of teacher-mediated vocabulary discussions during read alouds. During this intervention, fourteen second grade students participated in discussions of new vocabulary in the context of the text and their own lives. They discussed examples, non-examples, and synonyms for the targeted vocabulary. Fifteen comparison group students were incidentally exposed to the words during read alouds. Data sources included a multiple choice assessment, open ended assessment, and researcher log. An independent samples t-test was performed, and the intervention group’s mean gain vocabulary scores were significantly higher than the comparison group’s scores indicating the success of the intervention.
Keywords: Vocabulary acquisition; Read alouds; Primary schools